Incidência de displasia broncopulmonar em recém nascidos de muito baixo peso ao nascer e fatores associados - Tomé, Cindiamar (2018)
Bronchopulmonary dysplasia (BPD) is a neonatal lung disease with a significant impact on morbidity and mortality in preterm infants. Although several risk factors have been identified, BDP results from a complex interaction between the development of immature lungs and multiple pre and postnatal exposures. Interventions to reduce exposure have not reduced risk, suggesting a multifactorial etiology. This study aimed to determine the incidence of Bronchopulmonary Dysplasia and possible risk factors for the disease in preterm newborns with very low birth weight (<1500 g) hospitalized in the Neonatal Intensive Care Unit. An observational, retrospective cohort study involving 107 very low birth weight preterm infants admitted to a neonatal unit over a three-year period. Univariate and multiple logistic regression analysis was performed to determine the association of some variables (independent) with the occurrence of BPD (dependent variable). A significance level of p <0.05 was accepted. The incidence of BPD in the studied population was 39.3% (n = 42) and inversely proportional to gestational age at birth (p <0.05). In preterm infants (<28 weeks) it was 60.71%; in the very preterm infants (28-31.6) it was 48.89% and in the moderates (32-33.6) it was of 10.34%. No newborn with GA greater than 33.6 weeks developed BPD. Among the risk factors were the need for resuscitation in the delivery room, patent ductus arteriosus and early and late sepsis, which remained associated with multiple regression analysis. Early sepsis occurred in 80.95% (34) of the children who had BPD, and in 53.13% (34) of those who did not have BPD (p = 0.003). Likewise, late sepsis was prevalent in children with BPD, when compared to the others (90.48% X 50%, respectively, p <0.001). The reduction in the rate of infection seems to be an essential factor in reducing the prevalence of this disease.